PENGULANGAN TINDAK PIDANA ANAK YANG SEBELUMNYA PERNAH DILAKUKAN DIVERSI DI BALAI PEMASYARAKATAN SURAKARTA TAHUN 2014-2018 - ASNGARI, HASAN (Dinamika Hukum, 2019)
The purpose of this research is to examine and analyze the cause of the child to perform a criminal offence that had previously been in the version of Surakarta Correctional Hall. Reviewing and analyzing the implementation of supervision conducted by the Community Advisor of Surakarta Correctional Hall to the child in the version to avoid committing a criminal offence later in the day. The method of approach in writing is sociological juridical. The specification of this study uses descriptive. Data sources use primary data and skunder data. Data collection techniques using interviews and literature studies. To analyze the data, researchers use qualitative descriptive analysis methods. Based on the results of the study came the conclusion that the factors that cause the child to perform a criminal offence that had previously been conducted in the Surakarta Correctional Hall is due to economic factors, a factor of lack of affection and parental supervision, social environmental factors and lack of understanding and passion and practice of religious values and legal awareness factors. Economic factors are the most dominant cause factor, because because of the increasing economic needs where the needs of their lives are difficult to be fulfilled, so that they will be able to rebuild themselves to repeat the repetition Criminal. The form of supervision conducted by the Public advisor of Surakarta Correctional Hall to the child in the version to avoid repeated criminal acts, covering the initial stages of assessment, digging up the needs of what is needed The current client makes the goal to be achieved. The advanced stage is the process of mentoring Community advisers to assist clients in problems that are in a natural client. And the final stage, making a report of the termination that the child has had development during the guidance and able to return in the community and conduct supervision and maintenance on the client until the specified time. Keywords: repetition of crimes, versioned, child criminal justice system.